The role of life‐history traits, selective pressure and hydrographic boundaries in shaping the genetic structure of the transparent goby, Aphia minuta. (17th April 2015) - Ruggeri, Paolo; Splendiani, Andrea; Giovannotti, Massimo; Fioravanti, Tatiana; Occhipinti, Giulia; Nisi Cerioni, Paola; Caputo Barucchi, Vincenzo
Abstract: The transparent goby ( Aphia minuta ) is a small progenetic goby that displays a short life cycle with early reproductive maturity and represents a valuable fishery resource harvested by artisanal fleets in most part of its distributional range. This study aimed to define the genetic variability in A. minuta at five sampling sites within the Mediterranean Sea and one in the Atlantic Ocean through the analysis of 11 nuclear microsatellite loci. The results revealed that several genetic diversity estimators (expected and observed heterozygosities, mean number of alleles and allelic richness) were lower in the Atlantic Ocean than in the Mediterranean Sea, suggesting the role of past or current demographic events in shaping this pattern. The genetic structure was investigated using both classical genetic differentiation descriptors and Bayesian approaches, and by defining the current and past migration rates. The results obtained revealed a pronounced genetic structure within the Mediterranean Sea and suggest a very low current migration rate. The pattern of historical migration suggests the possible role of hydrographic boundaries in shaping the genetic structure detected in this species. In addition, the identification of loci under selection suggests the possible implication of selective pressures that are acting on genes connected with the peculiar life cycle of this gobiid fish.